Outcome of the glutaric aciduria type 1 (GA1) newborn screening program in Manitoba: 1980-2020 - Mhanni, Aziz; Aylward, Nicole; Boy, Nikolas; Martin, Bruce; Sharma, Atul; Rockman-Greenberg, Cheryl (Molecular genetics and metabolism reports, 2020)
Glutaric aciduria type 1 (GA1) is a severe inherited neurometabolic disorder whose clinical outcome has improved after implementation of newborn screening (NBS) programs and prompt beginning of guideline-directed presymptomatic metabolic treatment. We report the outcome of our 40-year experience with the diagnosis and management of GA1 which has improved but remains suboptimal.
Gesehen am 17.02.2022